ANALISIS HAMBATAN SAMPING PADA JALAN SUKA RAMAI KOTA LHOKSEUMAWE - Muzakir Muzakir; Sugiarto Sugiarto; Sofyan M. Saleh (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2020)
Lhokseumawe City has several roads, including: Medeka Street, Trade Street, Suka Ramai Street and others. This road is one of the local roads with a length of 0.56 km which has an important role in supporting the development of the trade and services sector in the region. However, improper use of parking spaces and street vendors causes traffic jams along most of the road. This research was conducted to find out how much the influence of side obstacles that cause disruption of road traffic flow so that the performance of the road is not in accordance with the requirements. This road performance analysis uses the Indonesian Road Capacity Manual (MKJI) method, Permen PU No. 19 of 2011 and Permen No. 34 of 2006 concerning roads. There are two data needed in this research, primary data and secondary data, primary data needed are side barriers, data recorded on observations are pedestrians (PK), vehicle parking (PK), In and out of vehicles (KM) and vehicles running slow (TOS). While for secondary data the data needed is a location map, Qanun number 1 of 2014 concerning the Regional Spatial Planning (RT / RW) of Lhokseumawe City. From data collection and processing for three days, namely Sunday, Monday and Thursday, the highest data was obtained on Monday, 10 September 2018 at 17:30 - 18:30 West Indonesia Time, namely the side barriers on all observation days were very high.